2021
DOI: 10.3390/jcm10091814
|View full text |Cite
|
Sign up to set email alerts
|

Acute Responses to Oxygen Delivery via High Flow Nasal Cannula in Patients with Severe Chronic Obstructive Pulmonary Disease—HFNC and Severe COPD

Abstract: Differences in oxygen delivery methods to treat hypoxemia have the potential to worsen CO2 retention in chronic obstructive lung disease (COPD). Oxygen administration using high flow nasal cannula (HFNC) has multiple physiological benefits in treating respiratory failure including reductions in PaCO2 in a flow-dependent manner. We hypothesized that patients with COPD would develop worsening hypercapnia if oxygen fraction was increased without increasing flow rate. We evaluated the acute response to HFNC in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, NIV has disadvantages, such as reduced comfort and poor interaction and synchronization between patients and ventilators, which are often difficult to identify and manage [ 26 ]. In recent years, HFNC has been increasingly applied in stabilizing and aggravating COPD patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, NIV has disadvantages, such as reduced comfort and poor interaction and synchronization between patients and ventilators, which are often difficult to identify and manage [ 26 ]. In recent years, HFNC has been increasingly applied in stabilizing and aggravating COPD patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…HFNC appears to be superior in terms of patient comfort and reduces complications of therapy. However, caution should be exercised in hypercapnic AECOPD as there is some evidence of worsening hypercapnia with higher FiO 2 for unchanged flow rates [ 34 ]. Further RCTs with large sample sizes are required to explore the direct comparison of HFNC versus NIV, especially with the advancement of both the nasal cannulae and high-flow oxygen delivery systems.…”
Section: Reviewmentioning
confidence: 99%
“…In a recent study, it has been reported that in HFNOT, the flow rate remains constant while the oxygen fraction is increased, which causes a deterioration in PaCO 2 . [ 13 ] A clinical question comparing the use of HFNOT with standard oxygen therapy and NIMV in exacerbations was evaluated, and recommendations were made in Section 6.9.1.…”
Section: 9 High-flow Nasal Oxygen Therapymentioning
confidence: 99%